A systematic review of the behaviours associated with depression in people with severe–profound intellectual disability. Issue 3 (11th January 2021) - Eaton, C.; Tarver, J.; Shirazi, A.; Pearson, E.; Walker, L.; Bird, M.; Oliver, C.; Waite, J.
Abstract: The assessment of depression in people with severe to profound intellectual disability (severe–profound ID) is challenging, primarily due to inability to report internal states such as mood, feelings of worthlessness and suicidal ideation. This group also commonly presents with challenging behaviours (e.g. aggression and self‐injury) with debate about whether these behaviours should be considered 'depressive equivalents' or are sensitive for, but not specific to, depression in severe–profound ID. We conducted a systematic review exploring behaviours associated with depression and low mood in individuals with severe–profound ID. The review was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (2009) guidelines. Three electronic databases were searched (Embase, PsycINFO and Ovid MEDLINE), and 13 studies were included and rated for quality. Few studies were rated as having high methodological quality. Behaviours captured by standard diagnostic schemes for depression (e.g. Diagnostic and Statistical Manual of Mental Disorders and International Classification of Diseases) showed a relationship with depression in severe–profound ID, including the two core symptoms (depressed affect and anhedonia), as well as irritability, sleep disturbance, psychomotor agitation, reduced appetite and fatigue. Challenging behaviours such as aggression, self‐injury, temper tantrums, screaming and disruptive behaviour were associated with depression. Challenging behaviours show a robust relationship with depression. Whilst these behaviours may suggest an underlying depression, study limitations warrant caution in labelling them as 'depressive equivalents'. These limitations include not controlling for potential confounds (autism, other affective disorders and pain) and bias associated with comparing depressed/non‐depressed groups on the same behavioural criteria used to initially diagnose and separate these groups. Future studies that use depressive measures designed for ID populations, which control for confounds and which explore low mood irrespective of psychiatric diagnosis, are warranted to better delineate the behaviours associated with depression in this population (PROSPERO 2018: CRD42018103244).